Effect of rhizobium on development, biomass accumulation and nodulation in Albizia procera seedlings from Himachal Pradesh - GHABRU, ARTI; RANA, NEERJA; MEENAKSHI, (Journal of Soil and Water Conservation, 2023)
For ecological balance and economic development of any nation forests are imperative. Studies on forest tree over various environmental conditions shows physiological and genetic variations associated with seeds source. Biological nitrogen fixation is an economic and environment-friendly technique by interacting with leguminous plants and helps in nitrogen availability. Nutrient upgrading of soils by symbiotic bacteria of legumes has been known for centuries. Present experiment was conducted with Albizia procera seeds of different locations inoculated with isolated bacteria of respective site and sown in poly bags. Results revealed that root inoculation of A. procera seedlings with Rhizobium was found significantly effective in improving biomass production and nodulation over the control. Shoot length of inoculated Albizia procera plants varied in the range from 11.89 to 15.4 cm, root length 8.05 to 12.89, nodule number from 1 to 5 and legheamoglobin content from 4.8 to 6.3 mg/g. Significantly maximum root length (12.89cm), shoot length (15.4cm). nodule number (5) and legheamoglobin content (6.3 mg/g) was observed with seedling of Baddi, Solan. Root inoculation showed significant effect in increasing interdependent traits and growth performances of Albizia procera seedlings. These conclusions illustrate to explore extensive research using Rhizobium as an inexpensive substitute for urea.